Evaluation of variable new antigen receptors (vNARs) as a novel cathepsin S (CTSS) targeting strategy - Smyth, P.; Ferguson, L.; Burrows, J. F.; Burden, R. E.; Tracey, S. R.; Herron, Ú. M.; Kovaleva, M.; Williams, R.; Porter, A. J.; Longley, D. B.; Barelle, C. J.; Scott, C. J. (Frontiers in Pharmacology, 2023)
Aberrant activity of the cysteine protease Cathepsin S (CTSS) has been implicated across a wide range of pathologies. Notably in cancer, CTSS has been shown to promote tumour progression, primarily through facilitating invasion and migration of tumour cells and augmenting angiogenesis. Whilst an attractive therapeutic target, more efficacious CTSS inhibitors are required. Here, we investigated the potential application of Variable New Antigen Receptors (vNARs) as a novel inhibitory strategy. A panel of potential vNAR binders were identified following a phage display panning process against human recombinant proCTSS. These were subsequently expressed, purified and binding affinity confirmed by ELISA and SPR based approaches. Selected lead clones were taken forward and were shown to inhibit CTSS activity in recombinant enzyme activity assays. Further assessment demonstrated that our lead clones functioned by a novel inhibitory mechanism, by preventing the activation of proCTSS to the mature enzyme. Moreover, using an intrabody approach, we exhibited the ability to express these clones intracellularly and inhibit CTSS activity whilst lead clones were also noted to impede cell invasion in a tumour cell invasion assay. Collectively, these findings illustrate a novel mechanistic approach for inhibiting CTSS activity, with anti-CTSS vNAR clones possessing therapeutic potential in combating deleterious CTSS activity. Furthermore, this study exemplifies the potential of vNARs in targeting intracellular proteins, opening a range of previously 'undruggable' targets for biologic-based therapy. Introduction Amongst lysosomal cysteine cathepsins, cathepsin S (CTSS) holds particular interest due to a range of distinctive properties including a normal restricted expression profile, inducible upregulation and activity across a broad pH range (